Occurrence Rate of Cyclops Lesion After Anatomic Double-Bundle ACL Reconstruction: Comparison Between Remnant Tissue Preservation and Resection Methods. Issue 10 (27th October 2022) - Hishimura, Ryosuke; Kondo, Eiji; Suzuki, Yuki; Matsuoka, Masatake; Iwasaki, Koji; Onodera, Tomohiro; Momma, Daisuke; Yagi, Tomonori; Yasuda, Kazunori; Iwasaki, Norimasa
Background: The occurrence rate of cyclops lesion after anatomic double-bundle anterior cruciate ligament (ACL) reconstruction with remnant tissue preservation remains unclear. Hypothesis: The study hypotheses were as follows: (1) the occurrence rate of cyclops lesion will be comparable between the remnant-preserving and remnant-resecting ACL reconstruction methods, and (2) there will be no significant differences in clinical outcomes between the remnant-preserving and remnant-resecting procedures. Methods: This retrospective comparative study involved 177 patients who underwent unilateral anatomic double-bundle ACL reconstruction using hamstring tendon autografts from 2014 to 2018 at our hospital. According to the Crain classification of ACL remnant tissue, 98 patients with remnant types I, II, or III underwent the remnant-preserving procedure (group A), and the remaining 79 patients with remnant type IV underwent the remnant-resecting procedure (group B). All patients underwent second-look arthroscopy. Patients were evaluated according to arthroscopic and clinical results at postoperative 15.2 ± 8.4 months (mean ± SD). Statistical comparisons between groups were made using the paired Student t test, chi-square test, and Fisher exact test. Study Design: Cohort study; Level of evidence, 3. Results: At second-look arthroscopy, the incidence of cyclops lesions was significantly higher in group B than in group A (29.1% vs 13.3%; P = .0139). Cyclops lesions were divided into 4 locations: femoral side (type 1), midsubstance (type 2), tibial side (type 3), and anterior (type 4) of the ACL graft. The ratio of the tibial-side cyclops lesion (type 3) was significantly higher in group B than in group A ( P = .0354). There were no significant differences in the clinical evaluation scores between the procedures. Side-to-side anterior laxity was significantly less in group A than in group B (0.7 vs 1.6 mm; P = .0035). Concerning postoperative laceration and synovium coverage of the grafts, group A was significantly better than group B ( P < .0001). Conclusion: In this cohort of patients undergoing double-bundle ACL reconstruction, resection of the ACL remnant was associated with a significantly higher rate of cyclops lesion formation when compared with preservation of the remnant.